Book review: Ziya Us Salam, Of Saffron Flags and Skullcaps. (December 2019) - Akram, Mohammad
Ziya Us Salam, Of Saffron Flags and Skullcaps. New Delhi: SAGE/ Select, 2018, 294 pp., ₹495 (paperback). ISBN: 978-93-528-0734-5.